Microbial dynamics during production of lesser mealworms (Alphitobius diaperinus) for human consumption at industrial scale. (April 2018) - Wynants, E.; Crauwels, S.; Verreth, C.; Gianotten, N.; Lievens, B.; Claes, J.; Van Campenhout, L.
Abstract: In this study, the microbial dynamics during an industrial production cyle of lesser mealworms ( Alphitobius diaperinus ), sold for human consumption, were characterised. The microbial numbers as well as the microbial diversity were generally higher for the substrate, existing of remaining feed, faeces and exuviae, than for the larvae. Most of the species-level operational taxonomic units, identified using Illumina MiSeq sequencing, that were present in the feed were also detected in the larvae and vice versa. However, bacterial diversity decreased in the larvae during rearing. These results suggested that the feed is an important determinant of the insect bacterial community, but that some bacterial species show a competitive advantage inside the insect gut and become dominant. A blanching treatment of the larvae after harvest reduced most microbial counts, but the number of aerobic endospores remained at 4.0 log cfu/g. Whereas food pathogens Salmonella spp., Listeria monocytogenes, Bacillus cereus or coagulase-positive staphylococci were not detected in our study, fungal isolates corresponding to the genera Aspergillus and Fusarium were recovered. Therefore, it cannot be excluded that mycotoxins were present. The results of this study contribute to a better understanding of the microbial dynamics and food safety aspects during the production of edible insects. Highlights: Microbial dynamics during production of lesser mealworm larvae were studied. The insect diet was an important source for the bacterial community in the larvae. During rearing, diversity in the larvae decreased and some species became dominant. Blanching reduced most counts, but a substantial amount of endospores remained. No food pathogens were detected, but possible mycotoxinogenic fungi were identified.